Acidificação de dejetos de suínos em compostagem automatizada: emissões gasosas de nitrogênio e resposta da alface à aplicação do composto no solo - Cantu, Rafael Ricardo (2014)
Automated pig slurry (PS) composting has been praised in Brazil by environmental agencies, pig farmers and agribusinesses as a promising strategy for the proper disposal of these residues. Nevertheless, one of the problems from composting is the ammonia (NH3) volatilization. Acidification of PS during composting is a possibility to circumvent this problem. However, is lake known about the agronomic value and the environmental impacts of materials generated in this process. The aim of this study was to evaluate the agronomic value and environmental impact on the NH3, N2O emissions and leaching of NO3-, of the organic compost obtained through automated pig slurry composting with and without acidification on lettuce. The study was conducted at the Federal University of Santa Maria, in the years 2011 to 2013, consisting of laboratory incubation experiments and field crops. In the study were assessed C and N mineralization of the compost in soil for 90 days in laboratory incubation. The treatments were: T1- Witness without application of compost; T2-Compost without acidification; T3-Compost acidification. In the field study, we evaluated the production and accumulation of N in lettuce fertilized with compounds in two successive crops in a total of 121 days. Urease (N-thiophosphate butiltriamida - NBPT) - In addition, the combination of the compost of nitrification inhibitors (dicyandiamide - DCD) and the compost without acidification with urea was evaluated, resulting in the following treatments: T1- control (Witness) without compost application or urea; T2- Witness associated with DCD and NBPT; T3-Compost without acidification; T4-Compost without acidification associated with NBPT and DCD; T5- Acidified compost; T6- Acidified compost associated with NBPT and DCD; T7-Organomineral consisting of the mixture of the compost non-acidified and urea; T8- Organomineral associated with NBPT and DCD; T9- Urea and T10- Urea associated with DCD and NBPT. The compost dosage used in both experiments was equivalent to 500 kg N ha-1. The C mineralization of the compost mixed with the soil was low (6.27% on average at 25oC) and was not affected by acidification, but this strategy reduced the N mineralization, causing immobilization. Even so, the compost acidification did not affect the production and N accumulation in lettuce or its environmental impact in crop. The compost provided an N accumulation increase of 30 kg ha-1 by lettuce and 1340 kg ha-1 in dry matter production in relation to control in crop field. Furthermore, emitted on average, 4.12 times less N2O that urea and had lower concentration of NO3-N in soil solution below the roots. Thus the use of the PS compost can be an interesting way of fertilization of crops, it provides the N accumulation, production increased, reduces the impacts to the environment and soil organic matter increases. The DCD and NBPT did not affect the lettuce production, however reduced the N2O and NH3emission and NO3-N concentration in the soil solution below the roots, when combined with urea and reduced the NO3-N levels in lettuce leaves when associated with the organic-fertilizer and urea.